Hippo pathway and protection of genome stability in response to DNA damage. (10th January 2016) - Pefani, Dafni E.; O'Neill, Eric
Abstract : The integrity of DNA is constantly challenged by exposure to the damaging effects of chemical and physical agents. Elucidating the cellular mechanisms that maintain genomic integrity via DNA repair and cell growth control is vital because errors in these processes lead to genomic damage and the development of cancer. By gaining a deep molecular understanding of the signaling pathways regulating genome integrity it is hoped to uncover new therapeutics and treatment designs to combat cancer. Components of the Hippo pathway, a tumor‐suppressor cascade, have recently been defined to limit cancer transformation in response to DNA damage. In this review, we briefly introduce the Hippo signaling cascade in mammals and discuss in detail how the Hippo pathway has been established as part of the DNA damage response, activated by apical signaling kinases that recognize breaks in DNA. We also highlight the significance of the Hippo pathway activator RASSF1A tumor suppressor, a direct target of ataxia telangiectasia mutated and ataxia telangiectasia and Rad3 related ATR. Furthermore we discuss how Hippo pathway in response DNA lesions can induce cell death via Yes‐associated protein (YAP) (the canonical Hippo pathway effector) or promote maintenance of genome integrity in a YAP‐independent manner. Abstract : Genomic instability is a driving force and hallmark of cancer. Induction of cell cycle checkpoints, DNA repair, chromatin remodelling and apoptosis are major mechanisms employed by cells to prevent the accumulation of DNA lesions. In this review we highlight the significance of the Hippo pathway in protection of genomic stability. Either as a cascade or independent components, Hippo pathway proteins regulate the aforementioned cell functions in response to stress to limit malignant transformation.